OVERPROTECTIVE PARENTING PATTERNS AND ITS INFLUENCE ON CHILDREN'S MENTAL HEALTH - Choirunnisa, Imtiyaz; Ramadhani, Fadhilla Elok; Syarifuddin, Syarifuddin; Safitri, Sani (PROGRES PENDIDIKAN, 2025)
Parenting plays an important role in the mental health and development of children. Overprotective parenting is one of the parenting styles that has received great attention in mental health research, which is characterized by excessive supervision and protection of children. This article aims to examine overprotective parenting and how it can affect children's mental health. The research method used in this study is a qualitative descriptive method. This method provides an in-depth understanding of a particular phenomenon or event, where in this study the researcher distributed a questionnaire as a tool to collect data. The results of this study indicate that 61.9% of children raised in an overprotective environment tend to have difficulty facing challenges, taking risks, and developing the social skills needed to succeed in life. In addition, they are more susceptible to mental health problems such as low self-esteem, depression, and anxiety.